The Ministry of Works and the Development of Souvenir Guides from 1955. (2nd October 2017) - Gill, David W. J.
Abstract : The first formal guidebooks for historic sites placed in state guardianship in the United Kingdom appeared in 1917. There was an expansion of the series in the 1930s and 1950s. However, from the late 1950s the Ministry of Works, and later the Ministry of Public Buildings and Works, started to produce an additional series of illustrated souvenir guides. One distinct group covered Royal Palaces: the Tower of London, Hampton Court Palace, Queen Victoria's residence of Osborne House on the Isle of Wight, and Holyroodhouse in Edinburgh. This was followed by guides for archaeological sites such as Stonehenge and Avebury, the Neolithic flint mines at Grime's Graves, the Roman villa at Lullingstone, and Hadrian's Wall. In 1961, a series of guides, with covers designed by Kyffin Williams, was produced for the English castles constructed in North Wales. These illustrated guides, some with colour, prepared the way for the fully designed guides now produced by English Heritage, Cadw, and Historic Environment Scotland.